Inhibition of side reactions and dendrite growth using a low-cost and non-flammable eutectic electrolyte for high-voltage and super-stable zinc hybrid batteries. Issue 15 (31st March 2023) - Deng, Yongqi; Wu, Yihan; Zhang, Kefu; Fan, Minghui; Wang, Lele; He, Yapeng; Yan, Lifeng
Abstract : A novel low-cost eutectic electrolyte of Zn(CH3 COO)2 /CH3 COOLi/urea has been prepared for high-voltage and super-stable zinc hybrid batteries with non-flammability and sustainability. Abstract : Electrolytes are important for long-life high-voltage aqueous zinc ion batteries (ZIBs) and dendrite-free Zn anodes. Here, we report a low-cost eutectic electrolyte composed of acetate and urea that expands the electrochemical stability window to >3.5 V with extremely low water contents and intrinsic non-flammability. Benefiting from the water-starved solvation structure, the Zn anode was protected from dendrite growth through the 3D diffusion of zinc ions and reduced parasitic side reactions. Besides, a wide electrochemical window enables zinc-based batteries with high operating voltage. Therefore, the assembled Zn//LiMn2 O4 battery achieved a high discharge plateau (∼1.9 V) and excellent capacity retention upon cycling. The optimized eutectogel perfectly inherits the advantages of liquid eutectic electrolytes while obtaining excellent mechanical properties, additionally fulfilling the application of quasi-solid-state flexible batteries under deformation conditions. The eutectic electrolyte has potential applications in high-voltage aqueous ZIBs which integrate performance, low cost, safety, and sustainability.